Sequencing of a novel HLA‐B allele, B*51:153, in a Spanish individual. Issue 4 (23rd August 2013) - Planelles, D.; Balas, A.; Sanz, G. F.; Rodríguez‐Cebriá, M.; Vicario, J. L.
<x xml:space="preserve">Abstract</x> HLA‐B*51:153 shows two nucleotide differences compared with B*51:08 at codon 163 (CTG>ACG), resulting in one amino acid replacement, 163L>163T.